Internalization of Sufism Values Among Intensive Female Students at the Al-Amien Prenduan Sumenap Islamic Studies Institute Campus - Fatin Khaironi; Andre Sutrisno (Values: Jurnal Kajian Islam Multidisiplin, 2025)
Internalization is the Union into the mind of the person or personality into a part of oneself. And efforts to instill divine and human values to students to clean the hearts of things that distance them from Allah SWT to form a good personality degan way of worship, habituation and training in the form of morals are commendable. The problem raised by the researcher is how the process of internalizing the values of Sufism among intensive students and what are the values of Sufism applied among intensive students at Al-amien prenduan campus.This study uses the type of case study research, the method used by the author in this study is to use a qualitative approach which is also called naturalistic research using descriptive analytical methods. This research also includes intense and in-depth research based on the phenomena contained in an institution.Based on the above research, the researchers concluded that the process of internalization of Sufism values among students is intensive through Ma'had activities: the process of internalization of Sufism values among students through activities to explore (Sufism). And through the stage of the process carried out by the cottage to the students in activities to inform the value of Sufism to students with taqwa, sincerity, love and pleasure